2021
DOI: 10.1002/anie.202108848
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl‐Glutarimides: Alternative Cereblon Binders for the Design of PROTACs

Abstract: Targeting cereblon (CRBN) is currently one of the most frequently reported proteolysis-targeting chimera (PRO-TAC) approaches,o wingt of avorable drug-like properties of CRBN ligands,i mmunomodulatory imide drugs (IMiDs). However,I MiDs are knownt ob ei nherently unstable,r eadily undergoing hydrolysis in body fluids.H ere we showt hat IMiDs and IMiD-based PROTACs rapidly hydrolyze in commonly utilized cell media, which significantly affects their cell efficacy.W ed esigned novel CRBN binders,p henyl glutarimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 35 publications
1
65
0
Order By: Relevance
“…138,139 In a study by Min and colleagues, significant changes in the thalidomide scaffold were executed. 140 Not only the phthalimide ring was replaced, but the nitrogen atom originating from the glutarimide precursor was also eliminated. Representative examples of phenyl glutarimides were obtained via a Suzuki cross-coupling between 62 and 4-hydroxyphenylboronic acid (Scheme 12).…”
Section: Alternative Crbn-binding Scaffoldsmentioning
confidence: 99%
“…138,139 In a study by Min and colleagues, significant changes in the thalidomide scaffold were executed. 140 Not only the phthalimide ring was replaced, but the nitrogen atom originating from the glutarimide precursor was also eliminated. Representative examples of phenyl glutarimides were obtained via a Suzuki cross-coupling between 62 and 4-hydroxyphenylboronic acid (Scheme 12).…”
Section: Alternative Crbn-binding Scaffoldsmentioning
confidence: 99%
“…To evaluate the feasibility of developing LCK degraders, we synthesized a series of PROTAC molecules that are composed of three components: (i) dasatinib as the LCK ligand with a reported dissociation constant (K d ) of 7 nM (28), (ii) a phenyl-glutarimide moiety as the cereblon-directing moiety (27), and (iii) a linker with varied composition to modulate activity and physicochemical properties (Fig. 1A).…”
Section: Development Of Lck Protacs and Their In Vitro Characterizationmentioning
confidence: 99%
“…However, IMiD-based PROTACs readily undergo hydrolysis, even in commonly used cell culture media, which can affect their cell efficacy. To address this, we have recently identified phenyl-glutarimide as an alternative cereblon binder with several advantages over classical IMiDs in PROTAC design, such as chemical stability, smaller size, lower polarity, greater ligand efficiency, and synthetic feasibility (27).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structural instability of CRBN binder thalidomide, the Rankovic lab discovered new CRBN binders with higher chemical stability and ligand efficiency in 2021 and designed a novel BET PROTAC molecule PROTAC 18 ( Table 1 ) with higher efficiency. Their data showed that PROTAC 18 can inhibit the viability of human acute myeloid leukemia MV4-11 cells at picomolar concentrations (IC 50 = 3 pM) [ 48 ]. Subsequently, Ciulli’s group designed a trivalent PROTAC molecule PROTAC 19 ( Table 1 ) based on MZ1 and the BET inhibitor MT1 that can bind to two BRD4 proteins, which carries two binding domains for BET proteins and one for the E3 binding domain to which ubiquitin ligase binds.…”
Section: Application Of Protac In Anticancermentioning
confidence: 99%